POLEMIK PENAFSIRAN DALAM HUBUNGAN SYURA DAN DEMOKRASI - Muhammad Taufik (Qaumiyyah: Jurnal Hukum Tata Negara, 2021)
Democracy is a concept that has developed in people's lives which originally came from the Western tradition. Democracy was only entered into the treasures of Islamic thought in the second half of the 19th century because it is a value system that can be applied in the context of people's lives, as a nation and state and does not conflict with Islamic values. At the beginning of the 20th century Islamic thinkers conducted a study of the relationship between Islam and democracy. Many Islamic thinkers view that democracy has positive values. Therefore, they tried to find the equivalent of the word democracy in Islamic teachings, then the term shura was invented. Shura is one of the teachings brought by the Prophet Muhammad, then practiced in Islam, especially in solving all life problems related to the affairs of the community, nation and state. Therefore, Islam is identified with the word shura, while the West is more familiar with the word democracy. However, in viewing the relationship between shura and democracy, the Mufassirs and Islamic intellectuals have different opinions. There was a polemic between them which has not been resolved until now. There are two different views regarding the relationship between shura and democracy. The first view, says that shura and democracy are two different things historically as well as their sources, shura comes from Islam while democracy comes from the West, therefore these two things are very contradictory. The second view is that between shura and democracy, although they have different origins, they have the same value content, among which they both hope for justice, equality and freedom. Therefore, shura and democracy are compatible and not contradictory. Abstrak Demokrasi merupakan salah satu konsep yang telah berkembang dalam kehidupan masyarakat yang awalnya berasal dari tradisi Barat. Demokrasi baru masuk dalam khazah pemikiran Islam pada paruh kedua Abad ke 19 karena merupakan sebuah sistem nilai yang dapat diterapkan dalam konteks kehidupan masyarakat, berbangsa dan bernegara dan tidak bertentangan dengan nilai-nilai Islam. Pada permulaan abad ke 20 para pemikir Islam melakukan kajian terhadap hubungan Islam dan demokrasi. Banyak dari kalangan pemikir Islam memandang bahwa demokrasi memiliki nilai-nilai positif. Karena itu, mereka berusaha mencari padanan kata demokrasi dalam ajaran-ajaran Islam, lalu ditemukanlah istilah syura. Syura merupakan salah satu ajaran yang dibawa oleh Nabi Muhammad, kemudian dipraktekkan dalam Islam, khususnya dalam menyelesaikan segala permasalahan kehidupan yang berkaitan dengan urusan masyarakat, bangsa dan Negara. Karena itu Islam diidentikkan dengan kata syura, sedangkan kalangan Barat lebih akrab dengan kata demokrasi. Namun, dalam melihat hubungan syura dan demokrasi, para Mufassir dan intelektual Islam berbeda pendapat. Terjadi polemik di antara mereka yang tidak terselesaikan hingga sekarang. Terdapat dua pandangan yang berbeda terkait dengan hubungan syura dan demokrasi. Pandangan pertama, mengatakan syura dan demokrasi adalah dua hal yang berbeda secara historis maupun sumbernya, syura bersumber dari Islam sedangkan demokrasi bersumber dari Barat karena itu kedua hal tersebut sangat bertentangan. Pandangan kedua, antara syura dan demokrasi walaupun mempunyai sumber asal yang berbeda, tetapi mempunyai kandungan nilai yang sama di antaranya sama-sama mengharapkan keadilan, persamaan dan kebebasan kareana itu, syura dan demokrasi sejalan dan tidak bertentangan.